An Extensive Study Regarding the Microscopic Anatomy of the Early Fetal Human Optic Nerve - Mihai Alin Publik; Florin Mihail Filipoiu; Adrian Vasile Dumitru; Andrei Precup; Ioan-Andrei Petrescu; Iulian Slavu; Raluca Florentina Tulin; Adrian Tulin; Andra Ioana Baloiu; Monica Mihaela Cirstoiu; Octavian Munteanu (MDPI AG, 2024)
The development of the optic nerve and its surrounding tissues during the early fetal period is a convoluted period because it spans both the organogenesis period and the fetal period. This study details the microscopic anatomy and histoembryology of the optic nerve in embryos during the early fetal period, including the second half of the first trimester of pregnancy. Serial sections through the orbit of variously aged embryos allowed us to analyze the nerve in both longitudinal and transverse aspects. A histological assessment and description of the structures surrounding and inside the nerve were performed, highlighting the cellular subtypes involved. By employing immunohistochemical techniques, we could characterize the presence and distribution of astrocytes within the optic nerve. Our findings suggest that by the 8th gestational week (WG) the structures are homologs to all the adult ones but with an early appearance so that maturation processes take place afterward. By this age, the axons forming the nerve are definitive adult axons. The glial cells do not yet exhibit adult phenotype, but their aspect becomes adult toward the 13th week. During its development the optic nerve increases in size then, at 14 weeks, it shrinks considerably, possibly through its neural maturation process. The morphological primordium of the blood-nerve barrier can be first noted at 10 WG and at 13 WG the morphological blood-nerve barrier is definitive. The meningeal primordium can be first noted as a layer of agglomerated fibroblasts, later toward 13 WG splitting in pachymeninx and leptomeninges and leaving space for intrinsic blood vessels.